Carbohydrate ingestion improves endurance performance during a 1 h simulated cycling time trial - El-Sayed, M. S.; Balmer, J.; Rattu, A. J. (Journal of Sports Sciences, 1997)
This study examined the effect of carbohydrate ingestion on metabolic and performance-related responses during and after a simulated 1 h cycling time trial. Eight trained male cyclists (VO2 peak = 66.5 ml kg-1 min-1) rode their own bicycles mounted on a windload simulator to imitate real riding conditions. At a self-selected maximal pace, the cyclists performed two 1 h rides (separated by 7 days) and were fed either an 8% carbohydrate or placebo solution. The beverages were administered 25 min before (4.5 ml kg-1) and at the end (4.5 ml kg-1) of the ride. With carbohydrate feeding, plasma glucose tended (P = 0.21) to rise before the time trial. Compared with rest, the plasma glucose concentration decreased significantly (P < 0.05) at the end of both rides, with no statistically significant difference being observed between treatments. Thereafter, plasma glucose increased significantly (P < 0.05) at 15 and 30 min into recovery, and was significantly higher at 30 min during the carbohydrate trial compared with the placebo trial. No significant changes in plasma free fatty acids were observed during the ride. However, a significant increase (P < 0.05) in free fatty acids was found at 15 and 30 min into recovery, with no difference between trials. Mean power output was significantly (P < 0.05) greater during the carbohydrate compared with the placebo trial (mean ± s.e.: 277 ± 3 and 269 ± 3 W, respectively). The greater distance covered in the carbohydrate compared with the placebo trial (41.5 ± 1.06 and 41.0 ± 1.06 km, respectively; P < 0.05) was equivalent to a 44 s improvement. We conclude that pre-exercise carbohydrate ingestion significantly increases endurance performance in trained cyclists during a 1 h simulated time trial. Although the mechanism for this enhancement in performance with carbohydrate ingestion cannot be surmised from the present results, it could be related to a higher rate of carbohydrate oxidation, or to favourable effects of carbohydrate ingestion on the central component of fatigue.